TINJAUAN HUKUM ISLAM TERHADAP PENARIKAN HIBAH MENURUT IMAM HANAFI DAN IMAM SYAFI’I - Maulana, Eksa; Masrokin; Afif, Abdullah (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2024)
Eksa Maulana. 2091014160. 2023. Review of Islamic Law Against Withdrawal of Grants According to Imam Hanafi and Imam Syafi'i. In people's lives, it often happens that a person who has donated his wealth to another person then takes back the property that has been donated, both a gift from parents to children and one person's gift to another person without any blood relationship. This could be because the grantor needed the property or because there were other reasons that made the grantor take back the property he had donated. As a result of this incident, it is certainly a record of the consideration of an Islamic Law and the views of the two Imams, in this case Imam Hanafi and Imam Syafi'i, to find a way to resolve the grant dispute, of course so as not to make the value of the essence of the gift bad among the community. The type of research used in this thesis is normative research, namely data sources obtained from primary and secondary data sources. In this study, the authors collected data by reading books, and other data sources related to this research in library research. Then it is analyzed using general deductive methods and then makes specific conclusions. From the results of the study it can be concluded that the withdrawal of grants is carried out by the grantor and the recipient of the grant by making decisions through the two legal concepts, namely Islamic Law and the legal views of the two Imams, namely Imam Hanafi and Imam Syafi'i, proportionally without either party discouraged. Keywords: Islamic Law, Imam Hanafi, Imam Syafi'i, Grant